Estudo sobre os efeitos biológicos da radiação gama da praia de Meaípe na cidade de Guarapari-ES - Zordan, Alan Bragança (2023)
Monazite sand deposits along certain beaches in Brazil have average external radiation levels of up to 20 µGy h -1 . However, there is a considerable gap in the literature regarding the effects of these low levels of natural radiation on biological systems. Samples of monazite-rich sand from Meaípe beach in southeastern Brazil were collected and analyzed by X-ray fluorescence, X-ray diffraction, and magnetic susceptibility. The natural terrestrial radiation from the beach sand showed positive correlation with the elements Th and Y, which are closely associated with Ce, Nd, Ca and P, suggesting that this grouping is mainly associated with the local natural radiation. The highest doses of gamma radiation are associated with the particle size fraction between 100 and 200 μm, and, the radioactive isotopes are present in the yellow fraction of the sand, which corresponds to approximately 14% by mass of each sample of the collected sands. It was observed that the samples collected during 12 months do not have a homogeneous composition, as they suffer changes in their composition coming from spatial variations, probably associated with the hydrogeological flows of the beach. A physical simulator of natural radiation with physicochemical parameters similar to the real beach conditions with monazite sand was built, to evaluate the biological effects of gamma radiation on E. coli, S. aureus and Chlorella sp., as study models. E. coli exposed to gamma radiation from the simulator for 1 day showed a 23.8% reduction in growth. S. aureus exposed to gamma radiation from the simulator for 1 day showed a reduction of 18.4% in growth. Electronic microscopy images showed morphological alterations in both microorganisms. Chlorella sp. exposed to gamma radiation from the simulator for 10 days showed a significant reduction of 30.16% in growth, increase of 10.85% in generation time, reduction of 7.61% in total protein content, increase of 15.61% in total lipid content, 6.74% increase in total antioxidant activity and 34.64% increase in autofluorescence. Characterization by CHNS organic analyzer did not show significant differences in carbon, hydrogen, nitrogen and sulfur contents. The percentage of mass obtained by EDS spectra also showed no changes in intracellular levels of calcium, sodium and magnesium.